Finite element simulation of bonding defects in cementing casing based on circumferential SH guided waves - Gong, Rui; Lyu, Yan; Song, Guorong; Gao, Jie; He, Cunfu (Frontiers in Materials, 2023)
The circumferential guide wave can effectively evaluate the damage of pipe or the cementation quality between pipe and peripheral medium. In this research, the state matrix method is applied to derive the circumferential SH waves dispersion equation of semi-infinite domain cement clad hollow circular pipe of steel matrix in cylindrical coordinate system. By combining the orthogonal basis of Legendre and Laguerre polynomial series, the circumferential SH waves dispersion curve of semi-infinite domain clad hollow circular pipe is numerically calculated. To investigate the interaction between circumferential SH waves and various cement bonding defects, a simulation model of the cemented casing structure was established using the finite element software ABAQUS. The model was designed to vary the defect parameters, providing a comprehensive understanding of cementing quality in cementing casing. Based on the numerical calculation results, it is concluded that the amplitude of the circumferential SH wave increases with the increase of the circumferential angle of the cement bonding defect. This approach serves as a basis for evaluating the effectiveness of circumferential SH waves in identifying cement bonding defects.